On One Leg: Trehalose Monoesters Activate Macrophages in a Mincle‐Dependant Manner. Issue 3 (16th January 2014) - Stocker, Bridget L.; Khan, Ashna A.; Chee, Stephanie H.; Kamena, Faustin; Timmer, Mattie S. M.
Abstract The C22 and C26 trehalose monoesters, each containing a single acyl chain, were synthesised in good overall yields and found to activate macrophages in a Mincle‐dependent manner. The activities of the monoesters paralleled those of their diester counterparts, and both mono‐ and diesters could activate the immune response in the absence of priming. This is the first time that trehalose monoesters have been found to activate macrophages, and these studies thus provide an important framework for the rational design of other Mincle agonists.